Sie sind auf Seite 1von 16

PROBLEM SECTION 3

∞ 1 ∞ 1
10. ∫ x −2 e−x dx = ∫ x −2+1−1 e−x dx
0 0

∞ 1
= ∫ x 2−1 e−x dx
0

1
= τ( )
2

= √π

∞ ∞
2 1 1
11. ∫ x 2 e−x dx = ∫ u e−u u−2 du
0 0 2

Dimisal 1 ∞ 1 −u
= ∫ u2 e du
𝑢 = 𝑥2 2 0
1
𝑢2 = 𝑥 1 ∞ 1+1−1 −u
1 −1 = ∫ u2 e du
𝑢 2 𝑑𝑢 = 𝑑𝑥 2 0
2
1 ∞ 3−1 −u
= ∫ u2 e du
2 0
1 3
= τ( )
2 2
∞ ∞ 1
3 1 2
12. ∫ xe−x dx = ∫ u3 e−u u−3 du
0 0 3

Dimisal 1 ∞ −1 −u
= ∫ u 3 e du
𝑢 = 𝑥3 3 0
1
𝑢3 = 𝑥 1 ∞ −1+1−1 −u
1 −2 = ∫ u 3 e du
𝑢 3 𝑑𝑢 = 𝑑𝑥 3 0
3
1 ∞ 2−1 −u
= ∫ u3 e du
3 0
1 2
= τ( )
3 3
1
1 32
0
1 3
13. ∫ x (ln ) dx =∫ (e−u )2 (ln −u ) . −e−u
0 x ∞ e
0
= ∫ e−2u (ln eu )3 . −e−u du
dimisal ∞

x = e−u = ∫ e−3u (u)3 du
0
dx = −e−u du ∞
1 31
= ∫ e−w ( w) dw
saat 0 3 3

x= 0→u= ∞ 1 ∞ −w
= ∫ e (w)3 dw
81 0
x=1→u=0
dimisal
1 ∞ 3+1−1 −w
= ∫ w e dw
w = 3u 81 0
1 ∞ 4−1 −w
1 = ∫ w e dw
𝑤=𝑢 81 0
3
1
= τ (4)
1 81
𝑑𝑤 = 𝑑𝑢 1
3 = 3!
81
3.2.1
=
81
2
=
27

1 0 1
3
14. ∫ √ln x dx = ∫ (ln e−u )3 . −e−u du
0 ∞
∞ 1
= − ∫ (−u)3 . e−u du
0
dimisal
∞ 1 1
x= e −u = − ∫ (−1)3 (u)3 . e−u du
0
−u
dx = −e du ∞ 1
= − ∫ (u)3 . e−u du
saat 0
∞ 1
x= 0→u= ∞ = − ∫ (u)3+1−1 . e−u du
0
x=1→u=0 ∞ 4
= − ∫ (u)3−1 . e−u du
0
4
= −τ ( )
3
1 1
= − 3 τ(3)
1
∞ 1 1 −3 −u 1

15. ∫ x −3 e−8x dx = ∫ ( u) e du
0 8 8
0
∞ 1 1 1
dimisal = ∫ (2−3 )−3 (u)−3 e−u du
0 8
u = 8x
1 ∞ 1 1
8
u=x = ∫ 2 (u)−3 e−u du
0 8
1
du = 𝑑𝑥 1 ∞ 1
8
= ∫ (u)−3 e−u du
4 0
1 ∞ 1
= ∫ (u)−3+1−1 e−u du
4 0
1 ∞ 2
= ∫ (u)3−1 e−u du
4 0
1 2
= τ( )
4 3
PROBLEM SECTION 7
1 1
dx 1 dy
3. ∫ =∫ 2
0 √1 − x 3 0 √1 − y 3y 3
dimisal 1 11 2
= ∫ (1 − y)−2 y −3 dy
x3 = y 0 3
2
x2 = y3 1 1 −2
= ∫ y 3 (1 − y)−1/2 dy
3 0
3x 2 dx = dy
1 1 −2+1−1 1
dy = ∫ y 3 (1 − y)−2+1−1 dy
dx = 2 3 0
3x
dy 1 1 1 1
dx = = ∫ y 3−1 (1 − y)2−1 dy
2 3 0
3y 3
1 1 1
= B( , )
3 3 2
1 1
1 τ (3) τ (2)
=
3 τ(5)
6
1
1 √π τ (3)
=
3 τ(5)
6
1 1
2 (1
3 dy
4. ∫ x = ∫ y (1 − y)2 1
0 0 2y 2
3
− x 2 )2 dx 1 1 1 3
= ∫ y 2 (1 − y)2 dy
Dimisal 2 0

y = x2 1 1 1+1−1 3
= ∫ y2 (1 − y)2+1−1 dy
1 2 0
x = y2
1 1 3−1 5
dy = 2x dx = ∫ y 2 (1 − y)2−1 dy
2 0
dy 1 3 5
dx = = B( ),( )
2x 2 2 2
dy 3 5
dx = 1 1 τ (2) , τ (2)
2y 2 =
2 τ4
1 1 31 1
1 2 τ (2) 2 2 τ (2)
= ( )
2 3!

3 1 1
1 8 τ (2) τ (2)
= ( )
2 3.2.1

1
= √π√π
32
π
=
32

y2 = B (3,3)
5. ∫ 6
dy
0 (1 + y) τ3 τ3
=
p−1=2 τ6
2! 2!
p=3 =
5!
p+q=6
2.2
3+q=6 =
5.4.3.2.1
q=3 1
=
30
∞ 1
y ∞
6. ∫ dy z3 dz
3 2 =∫
0 (1 + y ) 2 2
0 (1 + z) 3z 3
y3 = z 1
2
1 1 ∞ z −3
y2 = z 3
𝑝−1 = − = ∫ dz
3 3 0 (1 + z)2
3y 2 dy = dz 2
𝑝= 1 2 4
dz 3 = B( , )
dy = 𝑝+𝑞 = 2 3 3 3
3y 2 2 6 2 4
dz
+𝑞 = 1 (τ 3 , τ 3)
3 3 =
dy = 2 4 3 τ2
3z 3 𝑞=
3 1 21 1
= τ τ
3 33 3
1 2 1
= τ τ
9 3 3

π π
2 dθ 1 2 1
7. ∫ 1 = ∫ 2 (sin θ)−2 dθ
2 0
0 (sin θ)2
1 1
pemisalan = B ( , 0)
2 4
1
2p − 1 = − 1
2 1 τ(4)
=
1 2 τ(1)
2p = 4
2
1 1
p= =
4 2

2 2 (2𝑦)2
x 2 dx
8. ∫ =∫ 2𝑑𝑦
0 √2 − x 0 √2 − 2𝑦
Pemisalan 2 (2𝑦)2
=∫ 2𝑑𝑦
0 √2(1 − 𝑦)
𝑥 = 2𝑦 4 2 (𝑦)2
= ∫ 2𝑑𝑦
𝑑𝑥 = 2𝑑𝑦 √2 0 √(1 − 𝑦)
2
8
= ∫ 𝑦 2 (1 − 𝑦)−1/2 𝑑𝑦
√2 0
2
8 1
= ∫ 𝑦 3−1 (1 − 𝑦)2−1 𝑑𝑦
√2 0
8 1
= (1)𝐵(3 , )
√2 2
1
8 𝜏(3)𝜏 (2)
=
√2 𝜏 (7)
2
8 2.1√𝜋
=
√2 5 . 3 . 1 𝜏 (1)
2 2 2 2
8 . 2√𝜋
=
√2 5 . 3 . 1 √𝜋
2 2 2
8 8
= 2
√2 15
64
= 15 √2

Sketch the graph of 𝑥 3 + 𝑦 3 = 8 . Write the integrals for the following


quantities and evaluate them as B functions.

10. The first quadrant area bounded by the curve

𝑥3 + 𝑦3 = 8

𝑦3 = 8 − 𝑥3
1
𝐿 = ∫ 𝑦 𝑑𝑥
0

1
3
𝐿 = ∫ √8 − 𝑥 3 𝑑𝑥
0

8𝑑𝑦 8𝑑𝑦
𝑑𝑥 = 2
= 2
3𝑥
3.4𝑦 3
1
3
𝐿 = ∫ √8 − 𝑥 3 𝑑𝑥
0

1
3 8𝑑𝑦
𝐿 = ∫ √8 − 𝑥 3 𝑑𝑥 2
0 3.4𝑦 3
8 1 −2 3
= ∫ 𝑦 3 √8(1 − 𝑦) 𝑑𝑦
3.4 0

8.2 1 −2 3
= ∫ 𝑦 3 √(1 − 𝑦) 𝑑𝑦
3.4 0

4 1 −2 3
= ∫ 𝑦 3 √(1 − 𝑦) 𝑑𝑦
3 0

4 1 4
= 𝐵 ( , )
3 3 3

11. The centoid of this area

13
∫ 𝑥 𝑑𝐴 ∫0 √8 − 𝑥 3 𝑑𝑥
𝑥= 𝑥=
∫ 𝑑𝐴 13
∫0 √8 − 𝑥 3 𝑑𝑥
13
∫0 √8 − 𝑥 3 𝑑𝑥 1 1
3 8𝑑𝑦
𝑥= 13 ∫0 2𝑦 3 √(8 − 8𝑦)
∫0 √8 − 𝑥3 𝑑𝑥 3.4 𝑦 2/3
=
4 1 4
𝐵 (
3 3 , 3)
Misalkan
2.8 1 −13 3
3
𝑥 = 8𝑦 ∫0 𝑦 √(8 − 8𝑦) 8𝑑𝑦
= 3.4
4 1 4
𝐵 (
3 3 , 3)
𝑥 2 = 4 𝑦 2/3
8 1 23−1 4
−1
𝑥 = 2𝑦 1/3 ∫ 𝑦 (8 − 8𝑦) 3 8𝑑𝑦
= 3 0
4 1 4
𝐵 (
3 3 , 3)
3𝑥 2 𝑑𝑥 = 8 𝑑𝑦
2 4
8𝑑𝑦 𝐵(3 , 3)
𝑑𝑥 = 2 =2
3𝑥 1 4
𝐵 (3 , 3)
8𝑑𝑦
𝑑𝑥 = 2 4
3.4 𝑦 2/3 𝜏3,𝜏3
=2 𝜏2
1 4
𝜏3,𝜏3
5
𝜏3
2 5 2 5
𝜏3𝜏3 𝜏3𝜏3
=2 =2
1 1
𝜏3 𝜏3

12. The Volume Generated when the area is revolved about x axis

3 2
𝑉 = ∫ 𝜋𝑦 2 𝑑𝑥 = ∫ 𝜋( √8(1 − 𝑦)) 𝑑𝑥

3 2 8𝑑𝑦
Misalkan = ∫ 𝜋( √8(1 − 𝑦))
3.4 𝑦 2/3
8.4 3 2 𝑑𝑦
𝑥 3 = 8𝑦 = 𝜋 ∫( √(1 − 𝑦)) 2/3
3.4 𝑦
8 2 2
𝑥 2 = 4 𝑦 2/3 = 𝜋 ∫ 𝑦 −3 (1 − 𝑦)3 𝑑𝑦
3
𝑥 = 2𝑦1/3 8 1 5
= 𝜋 ∫ 𝑦 3−1 (1 − 𝑦)3−1 𝑑𝑦
3
3𝑥 2 𝑑𝑥 = 8 𝑑𝑦 8 1 5
= 𝐵( , )
3 3 3
8𝑑𝑦
𝑑𝑥 =
3𝑥 2

8𝑑𝑦
𝑑𝑥 =
3.4 𝑦 2/3
PROBLEMS SECTION 2

7. Verify L15 , L16, L17, and L18 by combining appropriate preceding formula
using (2.4)

𝐚𝟐
𝐋 𝟏𝟓 ∶ 𝐋 (𝟏 − 𝐜𝐨𝐬 𝐚𝐭) =
𝐩(𝐩𝟐 + 𝐚𝟐 )

L (1 − cos at) = L(1) − L(cos at)

1 p
= − 2
p p + a2

p 2 + a2 − p 2
=
p (p2 + a2 )

a2
= 𝐭𝐞𝐫𝐛𝐮𝐤𝐭𝐢
p (p2 + a2 )
𝐚𝟑
𝐋 𝟏𝟔 ∶ 𝐋 (𝐚𝐭 − 𝐬𝐢𝐧 𝐚𝐭) =
𝐩𝟐 (𝐩𝟐 + 𝐚𝟐 )

L (at − sin at) = L (at) – L (sin at)

= a L (t) – L (sin at)

1 a
=a −
p2 (p2 + a2 )

a a
= 2
− 2
p (p + a2 )

ap2 + a3 − ap2
=
p2 (p2 + a2 )

a3
= (𝐭𝐞𝐫𝐛𝐮𝐤𝐭𝐢)
p2 (p2 + a2 )

𝟐𝐚𝟑
𝐋𝟏𝟕 ∶ 𝐋( 𝐬𝐢𝐧 𝐚𝐭 – 𝐚𝐭 𝐜𝐨𝐬 𝐚𝐭) = 𝟐
(𝐩 + 𝐚𝟐 )𝟐
L( sin at – at cos at) = L( sin at) – a L(t cos at)
a a(p2 − a2 )
= −
(p2 + a2 ) (p2 + a2 )2
a (p2 + a2 ) − a(p2 − a2 )
=
(p2 + a2 )2
a p2 + a3 − ap2 + a3 )
=
(p2 + a2 )2
2a3
= (𝐭𝐞𝐫𝐛𝐮𝐤𝐭𝐢)
(p2 + a2 )2

𝐩
𝐋𝟏𝟖 ∶ 𝐋 (𝐞−𝐚𝐭 (𝟏 − 𝐚𝐭)) =
(𝐩 + 𝐚)𝟐

L (e−at (1 − at)) = L (e−at − ate−at )


= L (e−at ) − a L (te−at )
1 1
= −a
p+a (p + a)2
p+a−a
=
(p + a)2
p
= (𝐭𝐞𝐫𝐛𝐮𝐤𝐭𝐢)
(p + a)2

Find the inverse transform

2𝑝 − 1
10.
𝑝2
− 2𝑝 + 10
Menggunakan L13 dan
L14

2𝑝 − 1 2𝑝−1
𝐿−1 = 𝐿−1 ( )
𝑝2 − 2𝑝 + 10 (𝑝−1)2 +32
1 3 𝑝
= 𝐿−1 ( ) + 2 𝐿−1 ((𝑝−1)2+32 )
3 (𝑝−1)2 +32
1
= (𝑒 𝑡 sin 3𝑡) + 2 (𝑒 𝑡 cos 3𝑡)
3
1
= 𝑒 𝑡 ( sin 3𝑡 + 2 cos 3𝑡)
3
Menggunakan L7 dan L8 :
2𝑝 − 1
𝐿−1 ( 2 )
𝑝 − 2𝑝 + 10
Dicari akar-akarnya :
−𝑏 ± √𝑏 2 − 4𝑎𝑐
𝑥1,2 =
2𝑎
2 ± √4 − 4.1.10
=
2.1
2 ± √−36
=
2
2 ± 6𝑖
=
2
= 1 ± 3𝑖
𝑝2 − 2𝑝 + 10 = (𝑝 − (1 + 3𝑖))(𝑝 − (1 − 3𝑖))

2𝑝 − 1
𝐿−1 ( 2 )
𝑝 − 2𝑝 + 10
𝑝 1
= 2𝐿−1 ( )−𝐿
−1
( )
(𝑝 − (1 + 3𝑖))(𝑝 − (1 − 3𝑖)) (𝑝 − (1 + 3𝑖))(𝑝 − (1 − 3𝑖))

−(1 + 3𝑖)𝑒 (1+3𝑖)𝑡 + (1 − 3𝑖)𝑒 (1−3𝑖)𝑡 𝑒 (1+3𝑖)𝑡 + 𝑒 (1−3𝑖)𝑡


= 2[ ]−[ ]
−(1 + 3𝑖) + (1 − 3𝑖) −(1 − 3𝑖) + (1 + 3𝑖)
−2𝑒 (1+3𝑖)𝑡 − 6𝑖𝑒 (1+3𝑖)𝑡 + 2𝑒 (1−3𝑖)𝑡 − 6𝑖𝑒 (1−3𝑖)𝑡 𝑒 (1+3𝑖)𝑡 + 𝑒 (1−3𝑖)𝑡
=[ ]−[ ]
−(1 + 3𝑖) + (1 − 3𝑖) −(1 − 3𝑖) + (1 + 3𝑖)
𝑒 (1+3𝑖)𝑡 = 𝑒 𝑡 (cos 3𝑡 + 𝑖 sin 3𝑡)
𝑒 (1−3𝑖)𝑡 = 𝑒 𝑡 (cos 3𝑡 − 𝑖 sin 3𝑡)
Bagian kiri :
−𝟐𝒆(𝟏+𝟑𝒊)𝒕 − 𝟔𝒊𝒆(𝟏+𝟑𝒊)𝒕 + 𝟐𝒆(𝟏−𝟑𝒊)𝒕 − 𝟔𝒊𝒆(𝟏−𝟑𝒊)𝒕
=[ ]
−(𝟏 + 𝟑𝒊) + (𝟏 − 𝟑𝒊)
−𝟐(𝑒 𝑡 (cos 3𝑡+𝑖 sin 3𝑡))−𝟔𝒊(𝑒 𝑡 (cos 3𝑡+𝑖 sin 3𝑡))+
𝟐(𝑒 𝑡 (cos 3𝑡−𝑖 sin 3𝑡))−𝟔𝒊(𝑒 𝑡 (cos 3𝑡−𝑖 sin 3𝑡))
=
−𝟔𝒊
−𝟐((𝑒 𝑡 cos 3𝑡+𝑖 𝑒 𝑡 sin 3𝑡))−𝟔𝒊((𝑒 𝑡 cos 3𝑡+𝑖 𝑒 𝑡 sin 3𝑡))+
𝟐((𝑒 𝑡 cos 3𝑡−𝑖𝑒 𝑡 sin 3𝑡))−𝟔𝒊(𝑒 𝑡 (𝑒 𝑡 cos 3𝑡−𝑖𝑒 𝑡 sin 3𝑡))
=
−𝟔𝒊
−𝟒𝒊 𝑒 𝑡 sin 3𝑡−𝟏𝟐𝒊 𝑒 𝑡 cos 3𝑡
=
−𝟔𝒊
𝟐
= 𝑒 𝑡 sin 3𝑡 + 2 𝑒 𝑡 cos 3𝑡
𝟑
Bagian kanan :
−𝑒 (1+3𝑖)𝑡 +𝑒 (1−3𝑖)𝑡
=[ ]
−(1−3𝑖)+(1+3𝑖)

−𝑒(𝑒 𝑡 cos 3𝑡+𝑖 𝑒 𝑡 sin 3𝑡)+𝑒(𝑒 𝑡 cos 3𝑡−𝑖 𝑒 𝑡 sin 3𝑡)


=[ ]
6𝑖
−𝑒 𝑡 𝑖 sin 3𝑡−𝑒 𝑡 𝑖 sin 3𝑡
=[ ]
6𝑖
−2𝑒 𝑡 𝑖 sin 3𝑡
=[ ]
6𝑖
1 𝑡
= − 1𝑒 𝑖 sin 3𝑡
3

Jadi :
𝟐 1
= 𝟑 𝑒 𝑡 sin 3𝑡 + 2 𝑒 𝑡 cos 3𝑡 − 3 1𝑒 𝑡 𝑖 sin 3𝑡
1
= 𝑒 𝑡 ( sin 3𝑡 + 2 cos 3𝑡)
3
11. 𝐹(𝑝) Dicari akar-akarnya :
3𝑝 + 2 −𝑏 ± √𝑏 2 − 4𝑎𝑐
= 2 𝑥1,2 =
3𝑝 + 5𝑝 − 2 2𝑎
−5 ± √25 − 4(3)(−2)
=
2(3)
−5 ± √49
=
6
−5 ± 7
=
6
−5 + 7 2 1
𝑥1 = = =
6 6 3
−5 − 7 −12
𝑥2 = = = −2
6 6
1
3𝑝2 + 5𝑝 − 2 = 3 (𝑝 − ) (𝑝 − (−2))
3
1
= 3 (𝑝 − ) (𝑝 + 2)
3
3𝑝 + 2
𝐿−1 ( 2 ) 𝑝 2 1
3𝑝 + 5𝑝 − 2 = 𝐿−1 ( ) + 𝐿−1 ( )
1 3 1
(𝑝 − 3) (𝑝 + 2) (𝑝 − 3) (𝑝 + 2)

𝑝 2 1
=( )+ ( )
1 3 (𝑝 − 1) (𝑝 + 2)
(𝑝 − 3) (𝑝 + 2) 3
1 13𝑡 1
𝑒 − 2𝑒 −2𝑡
− 2 𝑒 𝑡
3 − 𝑒 −2𝑡
= ( 3 )+ ( )
1 3 1
− − 2 2+
3 3
1 1 1
− 𝑒 3𝑡 − 2𝑒 −2𝑡 2 𝑒 𝑡
3 − 𝑒 −2𝑡
=( 3 )+ ( )
7 3 7

3 3

1 1𝑡 6 −2𝑡 2 1𝑡 2 −2𝑡
= 𝑒3 − 𝑒 + 𝑒3 − 𝑒
7 7 7 7
3 1 4
= 𝑒 3𝑡 − 𝑒 −2𝑡
7 7
6−p
13. F(p) =
p2 + 4p + 20

a) Menggunakan L13 dan L14


6−𝑝 6−𝑝
𝐿−1 ( 2 ) = 𝐿−1 ( )
𝑝 + 4𝑝 + 20 (𝑝 + 2)2 + 42
4 𝑝+2
= 2 𝐿−1 ( 2 2
) + (−1)𝐿−1 ( )
(𝑝 + 2) + 4 (𝑝 + 2)2 + 42
= 2(𝑒 −2𝑡 sin 4𝑡) + (−1)(𝑒 −2𝑡 cos 4𝑡)
= 2𝑒 −2𝑡 sin 4𝑡 − 𝑒 −2𝑡 cos 4𝑡
= 𝑒 −2𝑡 (2 sin 4𝑡 − cos 4𝑡)
b) Menggunakan L7 dan L8 :

6−𝑝 Dicari akar-akarnya :


𝐿−1 ( 2 )
𝑝 + 4𝑝 + 20 −𝑏 ± √𝑏 2 − 4𝑎𝑐
𝑥1,2 =
2𝑎
−4 ± √42 − 4.1.20
=
2.1
−4 ± √−64
=
2
−4 ± 8𝑖
=
2
= −2 ± 4𝑖
𝑝2 + 4𝑝 + 20 = (𝑝 − (−2 − 4𝑖))(𝑝 − (−2 − 4𝑖))
= (𝑝 + (2 − 4𝑖))(𝑝 + (2 + 4𝑖))

6−𝑝 1
𝐿−1 ( ) = 6𝐿−1 ( )
𝑝2 + 4𝑝 + 20 (𝑝 + (2 − 4𝑖))(𝑝 + (2 + 4𝑖))
𝑝
−𝐿−1 ( )
(𝑝 + (2 − 4𝑖))(𝑝 + (2 + 4𝑖))
𝑒 −(2−4𝑖)𝑡 + 𝑒 −(2+4𝑖)𝑡
= 6[ ]
(2 + 4𝑖) − (2 − 4𝑖)
(2 − 4𝑖)𝑒 −(2−4𝑖)𝑡 + 𝑒 −(2+4𝑖)𝑡
−[ ]
(2 − 4𝑖) − (2 + 4𝑖)
6𝑒 (−2+4𝑖)𝑡 − 6𝑒 (−2−4𝑖)𝑡
=[ ]
(2 + 4𝑖) − (2 − 4𝑖)
2𝑒 (−2+4𝑖)𝑡 − 4𝑖𝑒 (−2+4𝑖)𝑡 −2𝑒 (−2−4𝑖)𝑡 − 4𝑖𝑒 (−2−4𝑖)𝑡
−[ ]
(2 − 4𝑖) − (2 + 4𝑖)
Bagian kanan :
=
2𝑒 (−2+4𝑖)𝑡 −4𝑖𝑒 (−2+4𝑖)𝑡 −2𝑒 (−2−4𝑖)𝑡 −4𝑖𝑒 (−2−4𝑖)𝑡
[ (2−4𝑖)−(2+4𝑖)
]

=
𝟐(𝑒 −2𝑡 (cos 4𝑡+𝑖 sin 4𝑡))−𝟒𝒊(𝑒 −2𝑡 (cos 4𝑡+𝑖 sin 4𝑡))−
𝟐(𝑒 −2𝑡 (cos 4𝑡−𝑖 sin 4𝑡))−𝟒𝒊(𝑒 −2𝑡 (cos 4𝑡−𝑖 sin 4𝑡))
−𝟖𝒊
−𝟒𝒊 𝑒 −2𝑡 sin 4𝑡−𝟖𝒊 𝑒 −2𝑡 cos 4𝑡
=
−𝟖𝒊
𝟏
= − 𝟐 𝑒−2𝑡 sin 4𝑡 + 𝑒−2𝑡 cos 4𝑡
Bagian kiri :
6𝑒 (−2+4𝑖)𝑡 −6𝑒 (−2−4𝑖)𝑡
=[ ]
(2+4𝑖)−(2−4𝑖)

=
6(𝑒 −2𝑡 cos 4𝑡+𝑖 𝑒 −2𝑡 sin 4𝑡)−6(𝑒 −2𝑡 cos 4𝑡−𝑖 𝑒 −2𝑡 sin 4𝑡)
[ ]
8𝑖
6𝑖𝑒 −2𝑡 sin 4𝑡+6𝑖𝑒 −2𝑡 sin 4𝑡
=[ ]
8𝑖
12𝑖𝑒 −2𝑡 sin 4𝑡
=[ ]
8𝑖
3
= 𝑒 −2𝑡 sin 4𝑡
2

Jadi :
3 𝟏
= 2 𝑒 −2𝑡 sin 4𝑡 − (− 𝟐 𝑒 −2𝑡 sin 4𝑡 +
𝑒 −2𝑡 cos 4𝑡)

= 2 𝑒 −2𝑡 sin 4𝑡 − 𝑒 −2𝑡 cos 4𝑡